Evaluation of the Diagnostic Accuracy of Percutaneous Core Needle Biopsy in Bone and Soft Tissue Tumors - Cengiz, T.; Yurtbay, A.; Muslu, O.; Simsek, S. Aydin; Ozbalci, A. B.; Coskun, H. S.; Dabak, N. (Galen SRO, 2024)
PURPOSE OF THE STUDY Open (incisional) biopsies have long been accepted as the gold standard in diagnosing bone and soft tissue tumors. However, the main disadvantage of this method is that it can lead to increased contamination, hematoma, infection, and pathological fracture. Compared to open biopsies, percutaneous core needle biopsies are less invasive, do not require hospitalization, have low costs and low complication rates, and there is no need for wound healing in cases that require radiotherapy. This study evaluated the diagnostic accuracy and reliability of percutaneous core needle biopsy. MATERIAL AND METHODS The study included the results of 250 percutaneous core needle biopsies of 244 patients who presented at the tertiary university hospital between September 2012 - September 2022 and were diagnosed with a bone or soft tissue tumor using the percutaneous core needle biopsy method and then underwent surgical excision in the Orthopaedics and Traumatology Clinic. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy rates were calculated for the percutaneous core needle biopsy method according to the compatibility of the results. RESULTS A fluoroscopy-guided percutaneous Jamshidi needle biopsy performed by an orthopedist for lesions originating from the bone has a diagnostic accuracy of 96%. CT-guided percutaneous Jamshidi needle biopsy performed by a radiologist for lesions originating from the bone has a diagnostic accuracy of 88.9%. Percutaneous Tru-cut needle biopsy performed by an orthopedist without imaging guidance for lesions originating from soft tissue has a diagnostic accuracy of 92%. USG-guided percutaneous Tru-cut needle biopsy performed by a radiologist for lesions originating from soft tissue has a diagnostic accuracy of 96,7% (p<0.001). DISCUSSION The diagnostic accuracy of open biopsies ranges from 91% to 99% in the literature. Additionally, the diagnostic accuracy of core needle biopsies in recent studies ranges from 76% to 99%. Compared to the literature, our study has shown that biopsies performed by orthopedic specialists have a high diagnostic power (96% for bone-derived lesions; 92% for soft tissue-derived lesions). CONCLUSIONS Percutaneous core needle biopsy is highly effective and reliable in diagnosing bone and soft tissue tumors. Managing patients by a team using a multidisciplinary approach will increase diagnostic success.
Keywords: Core Needle Biopsy; Percutaneous; Diagnostic Accuracy; Radiology Guided Biopsy; Bone and Soft Tissue Tumors